Gambaran Pengetahuan dan Perilaku Kebersihan Reproduksi Terkait Keputihan pada Remaja Putri di SMKN X Bekasi (STIKes Surya Global Yogyakarta, 2023)
Background: The reproductive system in women and men are different; the reproductive organs are sensitive organs that require special care. Knowledge about reproductive hygiene is important for adolescents because adolescents will enter puberty, some adolescents experience vaginal discharge before or after menstruation, there are also adolescents who experience abnormal/pathological vaginal discharge. The importance of knowledge is given to adolescents related to knowledge about reproductive hygiene and vaginal discharge in adolescent girls needs to understand vaginal discharge. When adolescent girls experience vaginal discharge they know how to maintain hygiene in their reproductive organs. According to (WHO, 2014), the number of adolescent reproductive health situations amounted to 1.2 billion or 18% of the world's population and 2010 as many as 43.5 million or about 18% of the population of Indonesia, Bogor regency is a district that is densely populated with a population of 5,331,149 people. The number of female population above the age of 10 years who have the highest diploma of junior high school and vocational school in 2015 is 807,931 people or about 15.15% of the total population of Bogor Regency because of the large population of adolescent girls and there are long-term effects on the reproductive health of adolescent girls in Bogor Regency. Based on the description above, this study is interested in taking samples of adolescent girls at SMKN X Bekasi. The aims of this research is to find out the description of knowledge and behavior of reproductive hygiene related to vaginal discharge in adolescent girls, because at that place no research has been conducted related to knowledge and behavior of reproductive hygiene related to vaginal discharge.Methods: This research was a descriptive study with a quantitative approach; primary data collection was obtained by direct collection through filling out questionnaires. Sampling in this study used probability sampling method, with simple random sampling, calculation using 10% Slovin formula,Results: The results of this study indicated that there were students as many as 34% of respondents with low knowledge and 46% of respondents behave badly from a total of 90 respondents.Conclusion: It can be concluded from this study that many students of SMKN X Bekasi have low knowledge and poor behavior.